Optimal fiscal policy in the presence of VAT evasion: the case of Bulgaria - Aleksandar Vasilev (Czech Journal of Economics and Finance, 2018)
This paper explores the effects of fiscal policy in the presence of a VAT evasion channel, and then compares and contrasts two regimes - the exogenous vs. optimal policy case. To this end, a dynamic general-equilibrium model, calibrated to Bulgarian data (1999-2014), is augmented with a government sector. The main findings from the computational experiments performed in the paper are: (i) The optimal steady-state income tax rate is zero; (ii) The benevolent Ramsey planner provides the optimal amount of the valuable public services, which are now three times lower; (iii) The size of the grey sector is twice lower; (iv) optimal steady-state consumption tax needed to finance the optimal level of government spending is twice lower, as compared to the exogenous policy case.
Keywords: D58; E26; H26; 330; consumption tax; income tax; VAT evasion; general equilibrium; fiscal policy; Bulgaria